The Advance of Technology of Reverse Transcriptase-Polymerase Chain Reaction in Identifying the Genome of Avian Influenza and Newcastle Diseases - Dyah Ayu Hewajuli; NLPI Dharmayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Avian Influenza (AI) viruses are zoonotic and caused death in humans. Newcastle Diseases (ND) virus has an economical impact in poultry. Therefore, the identification and characterization of AI and ND viruses that are appropriate, accurate and quick are important to protect human and poultry health. Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) was the latest gold standard to detect the genome of AI and ND viruses. Recently, RT-PCR was developed in routine diagnosis and research. RT-PCR is a method to amplify the sequences of DNA genome, preceded by reverse transcriptase process with the primer-mediated enzymatic. Some factors that influenced detection of AI and ND are design primer and probe, types of samples, enzyme, reagent composition, amplification temperature and cycles, technical and non-technical factors such as contamination and trained staff. Modified conventional and real time RT-PCR are able to improve the specificity and sensitivity of the test. Key words: Detection, Avian Influenza, Newcastle Diseases, RT-PCR